Visualizing melody with multiple acoustic and tagging values using the visualization module of the Oralstats tool - Adrián Cabedo Nebot (Estudios de Fonética Experimental, 2022)
This paper presents a way to visualize pitch patterns combiningmacoustic features (F0, intensity or duration) with other variables, like a basic notation on ToBI (Tone and Break Indices) or the projection of acoustic transformations, following MAS (Melodic Analysis of Speech) model. This visualization and the previous data transformation leading to it have been carried out with Oralstats, a tool developed in R that is conceived to merge speech transcriptions with prosodic, linguistic, and other variables. Here, the multiple melodic visualizations available in Oralstats are exemplified with intonational phrases taken from a corpus of YouTubers. The complete interactive dashboard is freely available on Github.